ASSERTIVENESS AS A FACTOR OF STUDENTS’ CHOICE OF BEHAVIOR STRATEGIES IN SOCIAL INTERACTION - Blynova, Olena; Moiseienko, Viktoriia; Oksana; Burlakova, Iryna; Yevdokimova, Olena; Toba, Marianna; Popovych, Ihor (Revista Inclusiones, 2020)
The purpose of the study is to examine students’ assertiveness and their choice of behavior strategies in situations of social interaction. It considers assertive behavior as an ability to defend one’s rights, show positive and negative emotions, overcome social anxiety and adapt to social life. The research empirically investigates the correlation between students’ assertiveness and behavior strategies in conflict and in real situations of social interaction. Significant correlations with “competition” and “compromise” strategies (p<.05); indirect correlations of “adaptation” and “avoidance” strategies (p<.05) were established. The obtained results in the female sample were substantiated: between assertiveness and “compromise” (a direct correlation) and “adaptation” (an indirect correlation) (p<.05). In the male sample, assertiveness correlates with the “avoidance” strategy (p<.05). We maintain that internality at a statistically significant level correlates with assertiveness (р< .05). The obtained and substantiated empirical results about the students’ assertive behavior have scientific value. They should be operationalized into educational process. These results are useful for psychological consultancy, psychotherapeutic and training work.